IMPLEMENTASI KOTA LAYAK ANAK DI KABUPATEN DEMAK - Moh. Rohmat Said; Murtono Murtono; Sri Utaminingsih (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2017)
This study purpose  to determine the role and implementation of Child Friendly City  in Demak District from an educational point of view. This research is done in the school environment in Demak District with the object of research are principals, students, parents and school committee. Qualitative approach with qualitative descriptive technique used in this research. Data analysis was obtained from interviews conducted on education and culture offices, social offices, principals, school committees, students as well as parents and student questionnaires and observations from researchers. The result of the research (1) the KLA implementation indicator in education of two of the eight indicators is appropriate ie non-smoking areas that have been applied in public places and the implementation of child-friendly schools whereas there are six indicators that include: , early childhood education, 12-year compulsory education, means of traveling from and to school and recreation and recreation facilities. (2) the implementation of KLA in schools of six of the seven indicators is not yet optimal: business involvement in the fulfillment of children's rights, information facilities, non-smoking areas, 12-year compulsory education, means of traveling for children to and from schools as well as, child friendly school  and facilities creation and recreation  that is right.